Drought Tolerance and Water‐Use Efficiency of Biogas Crops: A Comparison of Cup Plant, Maize and Lucerne‐Grass. (28th April 2016) - Schoo, B.; Wittich, K. P.; Böttcher, U.; Kage, H.; Schittenhelm, S.
Abstract: The cup plant ( Silphium perfoliatum L.) is discussed as an alternative energy crop for biogas production in Germany due to its ecological benefits over continuously grown maize. Moreover, a certain drought tolerance is assumed because of its intensive root growth and the dew water collection by the leaf cups, formed by fused leaf pairs. Therefore, the aim of this study was to estimate evapotranspiration (ET), water‐use efficiency (WUE) and the relevance of the leaf cups for the cup plant's water balance in a 2‐year field experiment. Parallel investigations were conducted for the two reference crops maize (high WUE) and lucerne‐grass (deep and intensive rooting) under rainfed and irrigated conditions. Root system performance was assessed by measuring water depletion at various soil depths. Transpiration‐use efficiency (TUE) was estimated using a model approach. Averaged over the 2 years, drought‐related above‐ground dry matter reduction was higher for the cup plant (33 %) than for the maize (18 %) and lucerne‐grass (14 %). The WUE of the cup plant (33 kg ha −1 mm −1 ) was significantly lower than for maize (50 kg ha −1 mm −1 ). The cup plant had a lower water uptake capacity than lucerne‐grass. Cup plant dry matter yields as high as those of maize will only be attainable at sites that are well supplied with water, be it through a large soil water reserve, groundwater connection, high rainfall or supplemental irrigation.